History and status of local cotton Gossypium spp. in Argentina, Brazil, Colombia and Ecuador - Arriel, N.H.C.; Cerón, M.; Cardoso, K.C.M.; Dileo, Pablo Nahuel; González, C.; Hoffmann, L.V.; Jiménez, H.; Klein, Lorena Marina; Lima, M.M. de A.; Medina, C.; Larrañaga-Monsalve, J.F.; Monteros-Altamirano, Á.; et al. (Springer, 2023)
Cotton (Gossypium spp.) contains more than 45 diploid (2n = 26) and at least five allotetraploid (2n = 4x = 52) species. The five allotetraploid (genome A and D) lineages that belong to the primary gene pool are indigenous to the Americas, including G. barbadense, G. hirsutum, G. mustelinum (Northeast Brazil), G. darwinii endemic to the Galapagos Islands, and G. tomentosum Nutall ex Seemann endemic to the Hawaii Islands. Recently, two other species, G. ekmanianum and G. stephensii, have been characterized. This review attempts to describe the historical context and importance of the cotton economy in Argentina, Brazil, Colombia, and Ecuador during the pre and post-colonial and mention the status of conservation and characterization of cotton germplasm, and current national access to these genetic resources in each country. The document presents information about cotton agriculture and manufacture and its use by indigenous communities for clothing, ritual, and medicinal purposes, where G. barbadense was the only species used at the time. Although in the last century, upland commercial cultivars industrially belonging to the species G. hirsutum replaced the native cotton species in these four countries. Currently, native cotton species are maintained and conserved in national genebanks, although limited information is available, and more research is necessary to identify attributes that allow the countries to move forward in plant breeding initiatives. In terms of legislation, it was found that the four countries have legislation to regulate the processes of access to genetic resources, traditional knowledge, and the distribution of benefits for their conservation and use. Up to now, this information for the four South American countries is dispersed and generally included in publications of a varied nature such as scientific and technical.